Local Culture-Based Tanggai Dance Learning Material Content for Character Development in Higher Education (Universitas Negeri Semarang, 2022)
In character-based traditional dance learning, the concept of material content is included as a component that cannot be ignored in a lesson because the type of content of dance learning material includes cognitive, psychomotor and affective aspects which aim to develop teaching strategies through content material in the form of Concepts, Facts, Procedures and Principles in the learning process, which aims in the realm of art education to be able to shape the character of students as prospective teachers who are professional in the field of art education. This article uses a qualitative research method of interpretive analysis with the stages of analysis taken using theoretical studies and analysis in the field through direct interviews with the lecturer of the Tanggai Dance study at the Department of Performing Arts Education, PGRI University Palembang. The focus of the research is on the material content which includes concepts, facts, procedures and principles in the learning process of the Tanggai Dance at PGRI Palembang University. The research results are in the form of an analysis of findings that represent a strategic view that is structured in the concept of content-based material content based on character education in the learning process of the Tanggai Dance in Higher Education, not only that the content of material in character-based dance education can encourage the development of local arts which are seen primarily as a means to preserve in the realm of maintaining its original form.